The Domain-general vs. Domain-specific Role of Metacognition in Arithmetic Achievements - Nigar, Naima (2023)
Error monitoring and awareness associated with meta-cognition and inhibitory processes of cognitive control also play a role in academic achievement (Young & Fry, 2008; Hirsh & Inzlicht, 2010). Despite playing an important role in academic achievement, research has yet to investigate the relationship between error monitoring and awareness and arithmetic achievement. The role of metacognition on academic performance could be domain-general vs. domain-specific (Rinne & Mazzocco, 2014), depending on the participant's age (Bellon et al., 2020). In the present study, I developed some numeric and non-numeric error monitoring and awareness tasks to test their domain-general vs. domain-specific role in arithmetic achievement. Here, error monitoring was measured by post-error slowing (PES) and post-error change in accuracy (PECA), which are the parts of behavioural adjustments after committing an error. Past research found that post-error behavioural adjustments are modulated by response stimulus intervals (RSI; Danielmeier & Ullsperger, 2011). The RSI was also manipulated in a series of short vs. long RSIs in the error monitoring tasks. Error awareness was measured as a proportion of aware errors in the numeric and non-numeric error awareness tasks. Three studies were conducted. The first two studies (Chapters II and III) explored the relationship between error monitoring and arithmetic achievement. The third study (Chapter V) explored the relationship between error awareness and arithmetic achievement. Data were collected from children and adults to investigate the relationship between error monitoring and arithmetic achievement. However, data were only collected from adults for the error awareness study. It is found from the present research that RSI has a significant effect on PES and PECA in adults. PES was higher under short RSI(s) than long RSI(s). The effect of RSI on PES was not viable to investigate in children due to the problem of recruiting children during the pandemic. There were also some issues with the task design, discussed in Chapter IV. However, PECA was affected by task types and RSI in adults. No improvement but decrement in accuracy was observed after error trials, and accuracy got significantly lower under short RSI. The decline in accuracy after error trials was higher for the numeric error monitoring task. Children with better numeric error monitoring ability tended to show better arithmetic achievement. However, adults with better error monitoring showed a cautious response (Slower response) trend in solving arithmetic problems. This relationship was only found to be significant for children in Study I (Chapter II). Study 3 in Chapter V showed that adults who were more aware of their errors in the non-numeric error awareness task also showed higher arithmetic efficiency. However, this relationship was only significant when numeric error awareness was added to the model. On the contrary, adults who showed poorer arithmetic efficiency were more aware of their errors in the numeric error awareness task. It could be concluded from this thesis that error monitoring and awareness is a complex process. More extensive research is needed in this area, especially with children. It is essential to consider the processing speed due to practice effect and response bias while designing error monitoring and awareness tasks.